The peptide SCOOP12 acts on reactive oxygen species homeostasis to modulate cell division and elongation in Arabidopsis primary root - Guillou, Marie-Charlotte (Journal of experimental botany, 2022)
© The Author(s) 2022. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.